Literary information in China a history - Chen, Jack Wei; Detwyler, Anatoly; Liu, Xiao, (Professor of East Asian studies); Nugent, Christopher M. B., 1969-; Rusk, Bruce, 1972- (Columbia University Press, 2021)
"An expansive yet concise literary history that traces the organization of literary information in China at the levels of the word, the document, and the collection, introducing readers to how these organizing forms operate across time. The volume will provide critical introductions to cultural forms and technologies of information management, such as graphemes and sentences, lexicons and encyclopedias, anthologies and newspapers, and libraries and databases. The individual contributions will offer up-to-date introductions for scholars and students (both undergraduate and graduate) seeking to understand how Chinese graphs or characters are encoded at a linguistic level and through digital technology; how anthologies were organized and what writings were included; how newspapers and journals distributed literary writings in time and space; how libraries, archives, and museums developed from imperial repositories to public, academic, and state-run institutions; and how bibliographic writings provided the foundations for digital thematic research collections"--